Microcirculation Mini Review: Loven’s Reflex Is Reproduced in The Lungs and Contributes in Pathophysiology of High-Altitude Pulmonary Edema; A Hypothesis - Elawad, Bahaeldean E. (British Journal of Healthcare and Medical Research, 2024)
High altitude pulmonary edema is a serious potentially fatal state. This article hypothesizes that, Loven’s reflex is reproduced in the lungs and contributes to the pathophysiology of high altitude pulmonary edema. In conclusion, Loven’s reflex induces a positive feedback mechanism which exaggerates hypoxic pulmonary vasoconstriction, elevates pulmonary arterial pressure, and promotes the development of high altitude pulmonary edema.